Waqf Awareness for Majelis Taklim and Muslimah Organizations - Soediro, Achmad; Kusumawardani, Media; Farhan, Muhammad; Adhitama, Fardinant; Kesuma, Nilam (Faculty of Economics, Universitas Sriwijaya, 2023)
The implementation of community service with the theme